Spatiotemporal Texture Reconstruction for Dynamic Objects Using a Single RGB‐D Camera. (4th June 2021) - Kim, Hyomin; Kim, Jungeon; Nam, Hyeonseo; Park, Jaesik; Lee, Seungyong
Abstract: This paper presents an effective method for generating a spatiotemporal (time‐varying) texture map for a dynamic object using a single RGB‐D camera. The input of our framework is a 3D template model and an RGB‐D image sequence. Since there are invisible areas of the object at a frame in a single‐camera setup, textures of such areas need to be borrowed from other frames. We formulate the problem as an MRF optimization and define cost functions to reconstruct a plausible spatiotemporal texture for a dynamic object. Experimental results demonstrate that our spatiotemporal textures can reproduce the active appearances of captured objects better than approaches using a single texture map.